2005
DOI: 10.1161/01.atv.0000149377.90852.d8
|View full text |Cite
|
Sign up to set email alerts
|

Dual Effect of Angiotensin-Converting Enzyme Inhibition on Angiogenesis in Type 1 Diabetic Mice

Abstract: Objective-We analyzed the beneficial therapeutic effect of angiotensin converting enzyme inhibitor (ACEI) on both retinal and hind limb neovascularization in diabetic mice. Methods and Results-Diabetic mice (streptozotocin, 40 mg/kg) were treated with or without ACEI (Perindopril, 3 mg/kg per day) or AT1 receptor blocker (Candesartan, 20 mg/kg) for 4 months. Hind limb ischemia was then induced by right femoral artery ligature for 1 additional month. In the ischemic leg, angiographic score, capillary density, a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

9
69
0
1

Year Published

2006
2006
2017
2017

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 102 publications
(79 citation statements)
references
References 39 publications
9
69
0
1
Order By: Relevance
“…Three weeks after the onset of ischemia, vessel density was evaluated by three different methods, as previously described 19,20 : 1) high-definition microangiography using barium sulfate (1 g/ml) injected in the abdominal aorta, followed by image acquisition with a digital X-ray transducer and computerized quantification of vessel density expressed as a percentage of pixels per image occupied by vessels in the quantification area; 2) assessment of capillary density in gastrocnemius muscle by immunostaining with a rabbit polyclonal antibody directed against total fibronectin (dilution 1/50; Chemicon Int., Temecula, CA) and morphometric quantification using Histolab software (Microvisions, Paris, France); and 3) laser Doppler perfusion imaging to assess in vivo tissue foot perfusion.…”
Section: Quantification Of Neovascularization In the Hindlimbmentioning
confidence: 99%
“…Three weeks after the onset of ischemia, vessel density was evaluated by three different methods, as previously described 19,20 : 1) high-definition microangiography using barium sulfate (1 g/ml) injected in the abdominal aorta, followed by image acquisition with a digital X-ray transducer and computerized quantification of vessel density expressed as a percentage of pixels per image occupied by vessels in the quantification area; 2) assessment of capillary density in gastrocnemius muscle by immunostaining with a rabbit polyclonal antibody directed against total fibronectin (dilution 1/50; Chemicon Int., Temecula, CA) and morphometric quantification using Histolab software (Microvisions, Paris, France); and 3) laser Doppler perfusion imaging to assess in vivo tissue foot perfusion.…”
Section: Quantification Of Neovascularization In the Hindlimbmentioning
confidence: 99%
“…The pro-angiogenic effects of ACE-Is on the microvasculature have been extensively studied in experimental animal and in vitro models: ACE-Is increased myocardial capillary density in SHRs, 12 in hind limb ischaemia of rabbits, 87 of mice 88,89 and in different rat models of obesity (Figure 2a, for specific review see Battegay et al 90 ). Inhibition of the breakdown of bradykinin (BK) and consecutive angiogenic activity of BK rather than angiotensin-IImediated effects most likely accounts for ACE-Itriggered angiogenesis (Figures 2a and b).…”
mentioning
confidence: 99%
“…Diabetes affects angiogenic and anti-angiogenic factors 17 and is associated with abnormal angiogenesis depending on the type of tissue. Neovascularization in some tissues such as the retina and impaired collateral formation in other tissues such as cardiac tissue suggest that diabetes differentially alters angiogeneic factors 18 . Published studies have reported that eNOS, VEGF and bFGF mRNA decrease during diabetes [19][20][21] .…”
Section: Discussionmentioning
confidence: 99%
“…In agreement with our results, a recent study reported that diabetes is associated with reduced neovascularization and that perindopril improved postischemic revascularization 19 . These authors suggested that the proangiogenic effect of ACE inhibitors was mediated at least in part by the bradykinin receptor and activation of VEGF and NO pathways 18,19 . In the present study, we found that enalapril increased serum NO and VEGF concentrations and reduced sVEGF-R1 concentrations in diabetic rats.…”
Section: Discussionmentioning
confidence: 99%